DEVELOPMENT PROSPECT OF TOURISM INDUSTRY IN MURSHIDABAD – JIAGANJ CD BLOCK, MURSHIDABAD DISTRICT, WESTBENGAL - ROY, SUBHAM KUMAR; MONDAL, CHUMKI (Revista de turism - studii și cercetări în turism, 2020)
Temporary movement of people from their place of birth or workplace to place of destination what they want to visit. Tourism is a growing industry it can help to employment generation and help to strength economy of country. Human environment interaction and quality of the environment is primary key to attract the tourist. This can lead to considerable pressure on the environment and in that process can accelerate the rate of environmental degradation. The main objectives of this paper are to identify the tourist spots surrounding study area, to draw the perception of tourist about the infrastructure and regarding problems and provide some probable recommendation for sustainable tourism development. To prepare this paper simple field based methodology are applied. Geo-informatics has been used for collecting data and prepare necessary map making. Various books, journals, report, were used for preparing secondary data source. Tourism should be undertaken with equity in mind, not to do unfair activities which make access or pollution free environment and appropriate economic use of natural and human environment. Through this paper we will provide some recommendations which are associated with eco friendly, sustainability and dynamic in nature.